Association between exposure to PM10 and lung function performance among construction workers / Nurulfarahana Md Noh - Md Noh, Nurulfarahana (2010)
The cross sectional study was done to determine the association between exposure of particulate matter (PM10) and lung function performance among construction workers. In addition to this, a correlation between PM10 concentrations and lung function performance was quantified and identification of the duration of employment that gives effect to the lung function performance among workers was evaluated. The study was carried out among thirty construction workers and thirty office workers. The personal exposure of PM10 was measured for both study groups using an personal air sampling pump. Lung function performance among the study group was measured using the vitalograph spirometer, were measurements of the FEV1%, FVC% and FEV1/FVC% were obtained. A Modified American Thoracic Society Questionnaire was used to gain the demographic data and respiratory symptoms of exposed and unexposed group Respondents comprised of three nationalities; Bangladeshi (16.7%), Indonesian (33.3%), and Malaysian (50%). Mean age, height and weight for exposed and unexposed group were 31.77±9.23, 31.87±9.33); 164.6±2.28, 167.6±2.48); and 70.2±4.48, 70.3±4.56 respectively. The study shows that there were significant differences between the concentration of PM10 among workers at the construction site and office workers (p<0.05). There were significant differences of negative correlation between concentration of PM10 and poor lung function performance among construction site workers (p<0.05). In addition to this, present respiratory symptoms was a significantly differences between the exposed and unexposed group (p<0.05). There were significant differences of the duration of employment of construction workers and poor lung function performance according to percentage value of FVC%,FEV1% and FEV1/FVC% among construction workers (r=-0.660,r=- 0.689,r=-0.568 ,p<0.05). The lung function performance of the respondents were not influenced by age, gender, weight and height. The construction site workers were highly exposed to PM10 due to many activities that produce high particulate matter such as excavating, grinding, reconstruction of building structure and grading of earthen materials. Moreover, the inhalation of the particulate matter during work cause deposition of small particles along the lining of alveoli that decreases the ventilation perfusion ratio and thus reduces the maximum oxygen uptake. This deposition may also be the cause of lower lung capacity. Even though the level of particulate matter was low, the study shows that there were significant association of concentration of PM-|0 and reduction of lung function performance.